TREATING CHRONIC SCHIZOPHRENIA AND COMPLEX TRAUMA THROUGH JUNGIAN DREAMWORK: A PRISON-BASED CASE STUDY: Received: 10 March 2025, Revised: 21 March 2025, Accepted: 08 August 2025, Date of Publication: 14 October 2025 - Dustin Warden (LIFE: International Journal of Health and Life-Sciences, 2025)
This case study documents the integrative treatment of a woman with chronic schizophrenia, complex PTSD, and comorbid anxiety and depression, incarcerated during the COVID-19 pandemic. Her primary symptoms included persistent hallucinations, trauma-driven nightmares, and emotional dysregulation. Traumatic themes of incest, supernatural forces, and violent dream figures dominated her inner world, exacerbated by institutional isolation, grief over a deceased brother, and unresolved family betrayal. Treatment combined Jungian dreamwork, guided hypnagogic induction, symbolic reframing, and trauma-focused narrative therapy. Hallucinatory content was interpreted as disowned psychic fragments; she was taught lucid dreaming, meditative coping skills, and dream preparation rituals. Through these techniques, she gained increasing agency in her dream life and began re-integrating dissociated parts of the self. Art assignments and metaphor-based dialogues enabled her to visualize and confront the “poltergeist” figure (a symbolic condensation of unresolved trauma and fear). Parallel work focused on dismantling distorted family loyalty and confronting historical abuse. She ultimately rejected financial dependency on her abuser, reasserted personal boundaries, and re-engaged with psychiatric care after initial resistance to medication. Her hallucinations diminished, and she reframed residual trauma as material for growth rather than doom. This case illustrates the power of symbolic and integrative interventions in treating schizophrenia complicated by developmental trauma. It further highlights the therapeutic challenges and innovations necessitated by pandemic-era incarceration.